Dilema Etik Dokter Membuka Rahasia Medis Pasien Menular Seksual ke Pasangan - Djai Yen Liauw; Elsa Monica Adriani; Aivi Mujono; Christa Adelia; James Gunawan; Jeceline Sutarto; Jonathan Naaman C; Klemens Andreas Charistio; Maria Raphaella G; Myra Antonia; Mela Dina Marie B; Yorisye Septiana (Jurnal MedScientiae, 2023)
Sexually transmitted diseases could be transmitted through unprotected vaginal, anal, and oral sex. Infectious diseases can cause various symptoms and even cause death in humans. One of the duties of a doctor is to prevent the spread of a disease, but in this scenario the doctor has to reveal the patient's identity to others. Various opinions and stigmas that arise in Indonesian society have made it more difficult for sexually transmitted diseases patients to reveal their condition even to their closest family. This increases the dilemma faced by doctors. Based on various aspects ranging from human rights, the right-to life, bioethics by adhering to the prima facie principle, as well as the convention law, the medical secrets of infectious disease patients must be disclosed to the family for togetherness' sake.